2010
DOI: 10.1242/dev.050351
|View full text |Cite
|
Sign up to set email alerts
|

Specific roles of Target of rapamycin in the control of stem cells and their progeny in theDrosophilaovary

Abstract: Stem cells depend on intrinsic and local factors to maintain their identity and activity, but they also sense and respond to changing external conditions. We previously showed that germline stem cells (GSCs) and follicle stem cells (FSCs) in the Drosophila ovary respond to diet via insulin signals. Insulin signals directly modulate the GSC cell cycle at the G2 phase, but additional unknown dietary mediators control both G1 and G2. Target of rapamycin, or TOR, is part of a highly conserved nutrient-sensing path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
161
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(174 citation statements)
references
References 73 publications
(126 reference statements)
12
161
0
1
Order By: Relevance
“…A similar role for stem cell maintenance was observed for Drosophila ovarian GSCs and mammalian hematopoietic stem cells, although the underlying mechanisms could be different (LaFever et al, 2010;Sun et al, 2010). For example, DE-cadherin expression was not altered in Tsc1/2 mutant germline stem cells (Sun et al, 2010), or in Tsc1/2 mutant imaginal disc cells (supplementary material Fig.…”
Section: Tsc1/2-torc1-s6k Signaling Regulates Ee Cell Differentiationmentioning
confidence: 58%
“…A similar role for stem cell maintenance was observed for Drosophila ovarian GSCs and mammalian hematopoietic stem cells, although the underlying mechanisms could be different (LaFever et al, 2010;Sun et al, 2010). For example, DE-cadherin expression was not altered in Tsc1/2 mutant germline stem cells (Sun et al, 2010), or in Tsc1/2 mutant imaginal disc cells (supplementary material Fig.…”
Section: Tsc1/2-torc1-s6k Signaling Regulates Ee Cell Differentiationmentioning
confidence: 58%
“…Interestingly, Tor has recently been shown to also have insulin-independent roles in germline stem cell proliferation in the Drosophila ovary. 13 We expected that disruption of the insulin signaling pathway would lead to degenerating egg chambers, resembling those seen in starved WT flies. Surprisingly, we found many abnormal Pwop egg chambers in which the NCs persisted and the FCs disappeared, indicating that PCD was initiated but incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…7 InR, chico, Akt, Tor, and S6k GLCs have a growth delay in which they produce only early stage egg chambers, indicating that insulin signaling is required to progress into mid oogenesis. 7,13 Because insulin signaling mutant egg chambers arrest before entering mid oogenesis, the early stages may be incompatible for the induction of PCD. DIAP1 levels remain high in early stage WT egg chambers but are reduced in mid-stage egg chambers, likely making them more vulnerable to starvation-induced PCD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The honeybee TOR pathway plays a key role in the development of queen bees, 34) the sole fertile individuals in the bee caste. 21) Moreover, it has been reported that TOR is required for the proliferation, growth, and survival of differentiating germ cells, 35) while germline stem cells and follicle stem cells in Drosophila ovaries have been found to respond to diet via IIS. 36) Taken together, these findings suggest that Egfr-mediated signaling and the subsequent control of fecundity through ovary maturation is mediated not only by RJ and royalactin, but also by FDRJ.…”
Section: )mentioning
confidence: 99%